Current developments in cell- and biomaterial-based approaches for stroke repair. (2nd January 2016) - Jendelová, Pavla; Kubinová, Šárka; Sandvig, Ioanna; Erceg, Slaven; Sandvig, Axel; Syková, Eva
Abstract : Introduction: Stroke is one of the most devastating diseases and a leading cause of mortality worldwide. So far, clinical management of stroke involves surgical clot retrieval or thrombolytic treatment inducing reperfusion of the occluded vessels in the cerebral infarcted area, which is dependent on early intervention following insult. New treatment strategies involve the promotion of angiogenesis and neuroplasticity, stimulation of endogenous neurogenesis, remyelinization, and immunomodulation by means of cell transplantation and sustained drug delivery. Areas covered: This review describes different types of stem cells (endogenous and exogenous neural progenitors, pluripotent stem cell derivatives, mesenchymal stem cells [MSCs], olfactory ensheathing cells) and biomaterials, their routes of administration, means of noninvasive imaging, and the prerequisites and hurdles for the successful translation of the cell therapies to the clinic. Expert opinion: Neural precursors (NPs) derived from pluripotent stem cells, unlike MSCs, can not only remodel the CNS by promoting neuroplasticity, angiogenesis, and immunomodulation, but also replace damaged cells. To transfer NPs into the clinic, step by step guidelines for researchers are identified and discussed.